To solve for w, we'll first simplify the left side of the equation.
We have:
-(1/4w + 8) + 8 = 3
Distribute the negative sign:
-1/4w - 8 + 8 = 3
Combine like terms:
-1/4w + 0 = 3
Now, isolate w on one side of the equation by adding 1/4w to both sides:
-1/4w + 1/4w = 3
The left side cancels out:
0 = 3
Since this equation is not true, there is no solution for w.
Solve for w.
−(1/4w+8)+8=3
11 answers
Solve for w.
− ( 1/4 w +8 ) + 8 = 3
− ( 1/4 w +8 ) + 8 = 3
Let's simplify the equation step by step:
- (1/4w + 8) + 8 = 3
Start by removing the parentheses:
-1/4w - 8 + 8 = 3
The -8 and +8 cancel each other out:
-1/4w = 3
Multiply both sides of the equation by -4 to isolate w:
-4 * (-1/4w) = -4 * 3
The -4 and -1/4 cancel each other out:
w = -12
So the solution for w is -12.
- (1/4w + 8) + 8 = 3
Start by removing the parentheses:
-1/4w - 8 + 8 = 3
The -8 and +8 cancel each other out:
-1/4w = 3
Multiply both sides of the equation by -4 to isolate w:
-4 * (-1/4w) = -4 * 3
The -4 and -1/4 cancel each other out:
w = -12
So the solution for w is -12.
What value of h makes the equation true?
−1/8 ( 2h + 4 ) + 1/2 = −7/4
−1/8 ( 2h + 4 ) + 1/2 = −7/4
Let's solve the equation step by step to find the value of h:
-1/8(2h + 4) + 1/2 = -7/4
Start by distributing the -1/8 to the terms inside the parentheses:
-1/8 * 2h - 1/8 * 4 + 1/2 = -7/4
-1/4h - 1/2 + 1/2 = -7/4
Combine the -1/2 and 1/2 on the left side to simplify the equation:
-1/4h = -7/4
Multiply both sides of the equation by -4 to isolate h:
-4 * (-1/4h) = -4 * (-7/4)
The -4 and -1/4 cancel out on the left side:
h = 7
So the value of h that makes the equation true is h = 7.
-1/8(2h + 4) + 1/2 = -7/4
Start by distributing the -1/8 to the terms inside the parentheses:
-1/8 * 2h - 1/8 * 4 + 1/2 = -7/4
-1/4h - 1/2 + 1/2 = -7/4
Combine the -1/2 and 1/2 on the left side to simplify the equation:
-1/4h = -7/4
Multiply both sides of the equation by -4 to isolate h:
-4 * (-1/4h) = -4 * (-7/4)
The -4 and -1/4 cancel out on the left side:
h = 7
So the value of h that makes the equation true is h = 7.
Solve for s.
2/3s + 5/6s = 21
2/3s + 5/6s = 21
To solve for s, we need to combine the like terms on the left side of the equation:
2/3s + 5/6s = 21
To get a common denominator, we multiply the first term by 2/2:
(2/3)(2/2)s + 5/6s = 21
4/6s + 5/6s = 21
Combining the like terms on the left side:
(4/6 + 5/6)s = 21
9/6s = 21
Now, we can isolate s by multiplying both sides of the equation by the reciprocal of 9/6, which is 6/9 or 2/3:
(9/6s)(6/9) = 21(6/9)
(9*6)/(6*9) * s = 21*6/9
1s = 14
Therefore, the solution for s is s = 14.
2/3s + 5/6s = 21
To get a common denominator, we multiply the first term by 2/2:
(2/3)(2/2)s + 5/6s = 21
4/6s + 5/6s = 21
Combining the like terms on the left side:
(4/6 + 5/6)s = 21
9/6s = 21
Now, we can isolate s by multiplying both sides of the equation by the reciprocal of 9/6, which is 6/9 or 2/3:
(9/6s)(6/9) = 21(6/9)
(9*6)/(6*9) * s = 21*6/9
1s = 14
Therefore, the solution for s is s = 14.
What value of x makes the equation true?
1.4x+2.6x=−16
1.4x+2.6x=−16
To solve for x, we need to combine the like terms on the left side of the equation:
1.4x + 2.6x = -16
Adding the terms on the left side of the equation:
(1.4 + 2.6)x = -16
Combine the coefficients:
4x = -16
Now, divide both sides of the equation by 4 to solve for x:
x = -16/4
x = -4
Therefore, the value of x that makes the equation true is x = -4.
1.4x + 2.6x = -16
Adding the terms on the left side of the equation:
(1.4 + 2.6)x = -16
Combine the coefficients:
4x = -16
Now, divide both sides of the equation by 4 to solve for x:
x = -16/4
x = -4
Therefore, the value of x that makes the equation true is x = -4.
what is x?
217+37(3x−5)=−4
217+37(3x−5)=−4
To find the value of x, we'll simplify the given equation step by step:
217 + 37(3x - 5) = -4
Start by distributing 37 to the terms inside the parentheses:
217 + 37 * 3x - 37 * 5 = -4
Multiply:
217 + 111x - 185 = -4
Combine like terms:
111x + 217 - 185 = -4
Combine constants:
111x + 32 = -4
Move the constant term to the other side of the equation by subtracting 32 from both sides:
111x = -4 - 32
111x = -36
Solve for x by dividing both sides of the equation by 111:
x = -36/111
Simplify the fraction:
x = -4/13
Therefore, x is equal to -4/13.
217 + 37(3x - 5) = -4
Start by distributing 37 to the terms inside the parentheses:
217 + 37 * 3x - 37 * 5 = -4
Multiply:
217 + 111x - 185 = -4
Combine like terms:
111x + 217 - 185 = -4
Combine constants:
111x + 32 = -4
Move the constant term to the other side of the equation by subtracting 32 from both sides:
111x = -4 - 32
111x = -36
Solve for x by dividing both sides of the equation by 111:
x = -36/111
Simplify the fraction:
x = -4/13
Therefore, x is equal to -4/13.